2004
DOI: 10.1152/japplphysiol.01128.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dust mite-induced asthma in cynomolgus monkeys

Abstract: Animal models exhibiting high homology with humans at the genetic and pathophysiological levels will facilitate identification and validation of gene targets underlying asthma. In the present study, a nonhuman primate model of allergic asthma was developed by sensitizing cynomolgus monkeys to dust mite antigen. Sensitization elevated allergen-specific serum IgE and IgG levels, and peripheral blood mononuclear cells isolated from sensitized animals released IL-4, IL-5, and IL-10, but not IFN-gamma. Aerosolized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 21 publications
(16 reference statements)
2
51
0
Order By: Relevance
“…In addition, natural sensitivity to dust mites had been documented in monkeys (24), increasing the relevance of the allergen. We added the subcutaneous injection in the sensitization by HDM because several studies showed that sensitization by subcutaneous injection with HDM could elicit allergen-specific IgE production (9) and allergic asthma symptoms (15,16). As we expected, the sensitization with HDM succeeded to induce asthmatic responses as well as DNP-As.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition, natural sensitivity to dust mites had been documented in monkeys (24), increasing the relevance of the allergen. We added the subcutaneous injection in the sensitization by HDM because several studies showed that sensitization by subcutaneous injection with HDM could elicit allergen-specific IgE production (9) and allergic asthma symptoms (15,16). As we expected, the sensitization with HDM succeeded to induce asthmatic responses as well as DNP-As.…”
Section: Discussionmentioning
confidence: 92%
“…For these reasons, actively immunized monkeys should be used for the development of asthma models. Several groups published articles about such models (15,16). The methods reported required a long term such as a halfyear or a year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations